The Influencing Factors of Job Satisfaction Among Teachers in Vocational Colleges in Sichuan Province - Chen, Pengyu; Butdisuwan, Sujin; Santaveesuk , Piyapun (International Journal of Development Administration Research, 2025)
The objectives of this research were: (1) To study teachers' job satisfaction in vocational colleges in Sichuan province; (2) To compare job satisfaction among teachers in the vocational colleges in Sichuan Province; and (3) To propose guidelines for improving college teacher job satisfaction in Sichuan Province. The research was a mixed-methods research, combining qualitative research and quantitative research. The population was teachers of five higher vocational colleges in Sichuan Province, totaling 4194. From the sampling totals, 100 people were taken as the sample size, respectively, i.e., the number of teacher samples collected from each school was 100, totaling 500 people. The key informants were selected from among these participants, obtained by a purposive sampling method. The instruments used for data collection were a semi-structured interview, a five-point rating scale questionnaire, and a focus group discussion. The statistics used for data analysis were descriptive statistical analysis, item analysis, reliability test, correlation analysis, multifactorial ANOVA, regression analysis, Structural Equation Modeling, and content analysis.